Hubungan Antara Status Gizi Dengan Kejadian ISPA Pada Anak Usia Toddler (1-3 Tahun) - Ria Rosanti; Feriana Ira Handyana; Agnis Sabat Kristianaa (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2020)
infancy by consulting directly with the nearest health service and various other references. Nutrition is an important intake that underlies physical development and mental toddler. Good nutritional status will optimize child development and strengthen the body's immune system, so the risk of developing Accute Respiratory Incidence (ARIs) will also be low. Thestudy is correlation study with cross sectional approach . The study was conducted in mart 23 until april 2018. Location for study at Bumiaji clinic center Batu City. Subject were toddler who visit in Bumiaji clinic center. Data sample taken with purposive sampling with total sampling and total is 53 respondens. Data takaen by techniques using the ISPA observation sheet and nutritional status counted by who-anthro. Data were analysis byLambdaformula. Based on the results of the analysis of nutritional status research, p value = 0,003 was obtained with r = 1,824 who stated that there was a relationship between nutritional status and the Accute Respiratory Incidence (ARIs) in toddler aged 1-3 years in the work area of ​​Bumiaji clinic Center, Batu City. Low nutritional status can trigger infectious diseases into the body, especially ARI. Toddler age children have a rudimentary physiological body so susceptible to disease if the nutritional status is not in control because it will decrease the immune system. This shows the importance of nutrition for children ages toddler. So that parents, especially mothers, must pay more attention to nutritional adequacy, especially during Keywords: Accute Respiratory Incidence (ARIs), Nutritional status, Toddler